(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Curcumin (CUR), a bioactive compound from Curcuma longa, has limited clinical utility due to poor solubility and low oral bioavailability. To overcome these challenges, this study developed mesoporous cyclodextrin nanosponge (CDNS)-based buccal tablets designed for enhanced, bioadhesive, and sustained curcumin delivery. Materials and Methods: Nanosponges (NSs) were synthesized through cross-linking and loaded with curcumin by freeze-drying. Buccal tablets were prepared by direct compression and optimized using Box-Behnken design. Characterization included particle size analysis, Fourier-transform infrared spectra, X-ray diffraction, differential scanning calorimetry, and evaluation of tablet physical properties, mucoadhesion, swelling, surface pH, in vitro drug release, and stability. Results: Curcumin-loaded NSs (95–139 nm) were smaller than plain NSs (140–180 nm) and exhibited low polydispersity with 20–35% drug loading. Spectroscopic and thermal analyses confirmed successful inclusion complex formation. Optimized tablets containing hydroxypropyl methylcellulose K4M (16.59%), Carbopol 934 (9.91%), and Chitosan (14.49%) showed acceptable physicochemical and mucoadhesive properties. In vitro studies demonstrated sustained curcumin release superior to the pure drug. Stability remained consistent over time. Conclusion: Mesoporous CDNS-based buccal tablets significantly improved curcumin’s solubility, mucoadhesion, and controlled release, representing a promising formulation for enhanced buccal drug delivery.